2012
DOI: 10.1016/j.jep.2012.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological basis for use of Lychnophora trichocarpha in gouty arthritis: Anti-hyperuricemic and anti-inflammatory effects of its extract, fraction and constituents

Abstract: Ethanolic extract of Lychnophora trichocarpha and some of its bioactive compounds may be promising agents for the treatment of gouty arthritis since they possesses both anti-hiperuricemic and anti-inflammatory properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
61
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(63 citation statements)
references
References 30 publications
1
61
0
1
Order By: Relevance
“…The mechanism of sesquiterpene lactones action against T. cruzi, including LYC, is still unknown. However, the presence of alkylant groups in the LYC molecule could be responsible for these activities (14,16,17,18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanism of sesquiterpene lactones action against T. cruzi, including LYC, is still unknown. However, the presence of alkylant groups in the LYC molecule could be responsible for these activities (14,16,17,18).…”
Section: Discussionmentioning
confidence: 99%
“…The anti-T. cruzi activity of LYC in vitro was first reported by Oliveira et al (14). This substance presents many other activities (15)(16)(17), including clastogenic and cytotoxic effects (18). Despite its pharmacological potential, the therapeutic application of LYC is limited due to its physicochemical properties that hamper oral administration, such as poor aqueous solubility, high lipophilicity (log P ϭ 5.03), and potential chemical instability in alkaline media (13).…”
mentioning
confidence: 97%
“…Its inhibitory activity against XOD has been confirmed in mice after oral ingestion. In addition, luteolin suppressed enhancement of hepatic XOD activity enhanced by oxonate which induces hyperuricemia [19,20]. Moreover, luteolin suppresses nitric oxide production by uric acid in pancreatic β-cells, which exacerbates diabetic complications [21].…”
Section: Backgroundsmentioning
confidence: 99%
“…In previous studies, eremantholide C and its oxidized derivatives showed activity against Trypanosoma cruzi (Oliveira et al 1996, Saúde-Guimarães et al 2007). Other biological/pharmacological activities were reported for eremantholide C, such as antibacterial, anti-hyperuricemic, anti-gouty arthritis, anti-inflammatory and antitumor (Barrero et al 2000, Saúde et al 2002, de Souza et al 2012, DÊNIA A. SAÚDE-GUIMARÃES, DÉLIO S. RASLAN, EGLER CHIARI and ALAÍDE B. DE OLIVEIRA Ferrari et al 2013, Saúde-Guimarães et al 2014).…”
Section: Introductionmentioning
confidence: 93%